Computing and Representing Sea Ice Trends: Toward a Community Consensus. (1st October 2013) - Wohlleben, T.; Tivy, A.; Stroeve, J.; Meier, W.; Fetterer, F.; Wang, J.; Assel, R.
Abstract : Estimates of the recent decline in Arctic Ocean summer sea ice extent can vary due to differences in sea ice data sources, in the number of years used to compute the trend, and in the start and end years used in the trend computation. Compounding such differences, estimates of the relative decline in sea ice cover (given in percent change per decade) can further vary due to the choice of reference value (the initial point of the trend line, a climatological baseline, etc.). Further adding to the confusion, very often when relative trends are reported in research papers, the reference values used are not specified or made clear. This can lead to confusion when trend studies are cited in the press and public reports.